2015
DOI: 10.1016/j.addbeh.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Positive affective states and alcohol consumption: The moderating role of trait positive urgency

Abstract: Trait positive urgency is characterised by risky and maladaptive actions in response to extreme positive affective states. Positive urgency has previously been shown to be a risk factor for alcohol consumption and alcohol-related problems, however, there has been limited experimental research examining how positive urgency may moderate relations between affective states and alcohol consumption. In the current study, a sample of 106 participants completed a trait measure of positive urgency and were then random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…For example, positive urgency predicted increased alcohol consumption on the bogus beer taste test following experimental induction of positive mood (Cyders et al, 2010). These findings were recently further expanded by Dinc and Cooper (2015) who revealed that this was true only for participants in a high arousal positive mood state. These results indicate that positive urgency might be a risk factor for increased alcohol use especially while individuals experience high arousal and high positive mood state.…”
Section: Impulsivity (Urgency) Emotional State and Alcohol Usementioning
confidence: 87%
See 1 more Smart Citation
“…For example, positive urgency predicted increased alcohol consumption on the bogus beer taste test following experimental induction of positive mood (Cyders et al, 2010). These findings were recently further expanded by Dinc and Cooper (2015) who revealed that this was true only for participants in a high arousal positive mood state. These results indicate that positive urgency might be a risk factor for increased alcohol use especially while individuals experience high arousal and high positive mood state.…”
Section: Impulsivity (Urgency) Emotional State and Alcohol Usementioning
confidence: 87%
“…The authors claim that alexithymia, which results from impaired processing of bodily sensations (including physiological arousal), underpins the urge to consume alcohol. Above (section 3 and 4), we described that not merely emotional state as such, but an emotional state with high arousal is associated with increased alcohol drinking particularly in highly impulsive individuals (for example Dinc and Cooper, 2015;Peacock et al, 2015).…”
Section: Emotional Processing Interoception and Alcohol Abusementioning
confidence: 94%
“…Additionally, there is considerable research linking positive mood based rash action to alcohol-related consequences (Arbeau et al, 2011; Cyders et al, 2009; Dinc and Cooper, 2015). The current study supports these findings, and suggests that indices of behavioral control may be particularly important when it comes to regulating positive-mood induced rash action.…”
Section: Discussionmentioning
confidence: 99%
“…Even though they are highly inter-correlated, differences in prediction between positive and negative urgency exist. For example, previous cross-sectional, longitudinal, and experimental emotion induction studies have demonstrated the distinctiveness of negative and positive urgency in risk-taking, such that negative urgency predicts negative emotion-based risk-taking while positive urgency predicts positive emotion-based risk-taking [ 7 , 35 , 54 , 71 , 72 ]. Additionally, only negative urgency is associated with binge eating [ 8 , 69 ] and positive urgency is significantly greater among individuals with high risk for mania compared to those with low risk (negative urgency did not differ between groups) [ 63 ].…”
Section: Brief Review Of Existing Research With the Upps-p Modelmentioning
confidence: 99%